2018
DOI: 10.1007/s41669-018-0085-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Idiopathic Pulmonary Fibrosis Progression on Healthcare Resource Use

Abstract: Background Disease progression and acute exacerbations in patients with idiopathic pulmonary fibrosis (IPF) are associated with high morbidity and mortality. They usually require a visit to a specialist or a general practitioner (GP) in less severe cases or hospitalisation in more severe cases. Objective The objective of this study was to identify factors that influence resource use in IPF. Methods Clinical and healthcare resource use data were collected in two large, international, multi-centre, randomised co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This is consistent with our earlier study based on the PHD, [ 9 ] but lower than observed in other observational studies, in which the mean or median length of stay ranged from 8.3 to 10.6 days. [ 5 , 7 , 10 , 13 ] In our study, length of stay was longer in patients with pneumothorax or pneumonia, and in patients admitted to the ICU or receiving mechanical ventilation. Approximately 30% of patients hospitalized in our study were readmitted to hospital within 90 days, with admission to hospital within the previous year the strongest predictor of readmission.…”
Section: Discussionmentioning
confidence: 55%
“…This is consistent with our earlier study based on the PHD, [ 9 ] but lower than observed in other observational studies, in which the mean or median length of stay ranged from 8.3 to 10.6 days. [ 5 , 7 , 10 , 13 ] In our study, length of stay was longer in patients with pneumothorax or pneumonia, and in patients admitted to the ICU or receiving mechanical ventilation. Approximately 30% of patients hospitalized in our study were readmitted to hospital within 90 days, with admission to hospital within the previous year the strongest predictor of readmission.…”
Section: Discussionmentioning
confidence: 55%
“…The median length of hospital stay was 5 days. This is shorter than the lengths of stay reported in previous real-world studies and clinical trials, which have ranged from 7 to 10.2 days [3, 7, 8, 20, 27], likely reflecting differing patient populations and healthcare systems. Length of stay was 32% longer in patients receiving intensive care.…”
Section: Discussionmentioning
confidence: 64%